Note : All calculations will be done in SI.
It means that
"\\left\\{\\begin{array}{l}\nm=64\\,\\,lbs\\approx 29.03\\,kg\\\\[0.3cm]\n\\Delta x=8\\,\\,feet\\approx 2.44\\,\\,m\\\\[0.3cm]\nl_0=3\\,\\,feet\\approx 0.92\\,\\,m\\\\[0.3cm]\ng\\approx 9.81\\,\\,m\/s^2\n\\end{array}\\right."
1 STEP : Find the stiffness of the spring
(more information : https://en.wikipedia.org/wiki/Hooke%27s_law)
In our case,
"mg=k\\cdot\\Delta x\\to k=\\frac{mg}{\\Delta x}\\approx\\frac{29.03\\cdot9.81}{2.44}\\approx116.72\\,\\frac{N}{m}"
2 STEP : Let's describe all the forces that act on our body
"\\text{The force of gravity} - F_g=mg\\\\[0.3cm]\n\\text{Hooke's force}- F_s=-kx\\\\[0.3cm]\n\\text{damping force}-F_d=-8\\cdot v\\equiv-8\\cdot\\frac{dx}{dt}\\\\[0.3cm]\n\\text{an external force}- f(t)=6t^2" 3 STEP : Let's write the equation of motion (Newton's second law) for a given body, together with the initial conditions
"m\\vec{a}=\\vec{F_g}+\\vec{F_s}+\\vec{F_d}+\\vec{f}(t)\\\\[0.3cm]\nx(0)=l_0\\approx0.92\\,m\\\\[0.3cm]\nx'(0)=0"Suppose that all movement occurs in the vertical direction, the axis is directed along the action of the force of gravity. Here is the corresponding figure.
Note: since the forces of Hooke, dumping and one more act in the same direction, for the convenience of reading the diagram, I will draw from NOT from one point.Since the direction of the external force is not indicated, then I myself will choose its direction.
"Oy : m\\cdot\\overbrace{a}^{x''}=mg-8\\overbrace{v}^{x'}-116.72\\cdot x+6t^2\\\\[0.3cm]\n29.03\\cdot x''+8\\cdot x'+116.72\\cdot x=29.03\\cdot 9.81+6t^2"This is an inhomogeneous second-order equation with constant coefficients. The solution has the form
"x(t)=x_{hom}(t)+x_{part}^{(1)}+x_{part}^{(2)},\\,\\,\\text{where}\\\\[0.3cm]\nx_{hom}(t) : 29.03\\cdot x''+8\\cdot x'+116.72\\cdot x=0\\\\[0.3cm]\nx(t)=e^{\\lambda t}\\to x'(t)=\\lambda\\cdot e^{\\lambda t}\\to x''(t)=\\lambda^2\\cdot e^{\\lambda t}\\\\[0.3cm]\n\\left.29.03\\cdot \\lambda^2\\cdot e^{\\lambda t}+8\\cdot \\lambda\\cdot e^{\\lambda t}+116.72\\cdot e^{\\lambda t}=0\\right|\\div e^{\\lambda t}\\\\[0.3cm]\n29.03\\cdot \\lambda^2+8\\cdot \\lambda+116.72=0\\\\[0.3cm]\n\\sqrt{D}=\\sqrt{8^2-4\\cdot29.03\\cdot116.72}\\approx 116.14\\cdot i\\\\[0.3cm]\n\\left[\\begin{array}{l}\n\\lambda_1=\\displaystyle\\frac{-8-116.14\\cdot i}{2\\cdot29.09}\\approx-0.14-2i\\\\[0.3cm]\n\\lambda_2=\\displaystyle\\frac{-8+116.14\\cdot i}{2\\cdot29.09}\\approx-0.14+2i\n\\end{array}\\right.\\\\[0.3cm]\nx_{hom}(t)=A_1\\cdot e^{(-0.14-2i)t}+A_2\\cdot e^{(-0.14+2i)t}\\to\\\\[0.3cm]\n\\boxed{x_{hom}(t)=C_1e^{-0.14t}\\cdot\\cos{2t}+C_2e^{-0.14t}\\cdot\\sin{2t}}"
It remains to find partial solutions :
"x_{part}^{(1)} : 29.03\\cdot x''+8\\cdot x'+116.72\\cdot x=29.03\\cdot 9.81\\\\[0.3cm]\nx(t)=Const\\to x'(t)=0\\to x''(t)=0\\to\\\\[0.3cm]\n29.03\\cdot 0+8\\cdot 0+116.72\\cdot Const=29.03\\cdot 9.81\\to\\\\[0.3cm]\nConst=\\frac{29.03\\cdot 9.81}{116.72}\\approx2.44\\to\\boxed{x_{part}^{(1)}=2.44}\\\\[0.3cm]\nx_{part}^{(2)} : 29.03\\cdot x''+8\\cdot x'+116.72\\cdot x=6t^2\\\\[0.3cm]\nx(t)=At^2+Bt+C\\to x'(t)=2At+b\\to x''(t)=2A\\to\\\\[0.3cm]\n29.03\\cdot 2A+8\\cdot(2At+B)+116.72\\cdot(At^2+Bt+C)=6t^2\\to\\\\[0.3cm]\n116.72At^2+(116.72B+16A)t+(116.72C+8B+48.06A)=6t^2\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\n116.72A=6\\\\[0.3cm]\n116.72B+16A=0\\\\[0.3cm]\n116.72C+8B+48.06A=0\n\\end{array}\\right.\\to \\left\\{\\begin{array}{l}\nA\\approx 0.05\\\\[0.3cm]\nB\\approx-0.007\\\\[0.3cm]\nC\\approx-0.02\n\\end{array}\\right.\\\\[0.3cm]\n\\boxed{x_{part}^{(2)}=0.05t^2-0.007t-0.02}"
Conclusion, general solution is
"x(t)=x_{hom}(t)+x_{part}^{(1)}+x_{part}^{(2)}\\\\[0.3cm]\nx(t)=e^{-0.14t}\\cdot\\left(C_1\\cos{2t}+C_2\\sin{2t}\\right)+0.05t^2-0.007t+2.42"
Now let's find the constants, for this we use the initial conditions:
"x(0)\\approx0.92=1\\cdot(C_1\\cdot1+C_2\\cdot0)+2.42\\to\\\\[0.3cm]\nC_1=0.92-2.42=-1.5\\to\\boxed{C_1=-1.5}\\\\[0.3cm]\nx'(t)=-0.14e^{-0.14t}\\cdot\\left(C_1\\cos{2t}+C_2\\sin{2t}\\right)+\\\\[0.3cm]\n+e^{-0.14t}\\cdot\\left(-2C_1\\sin{2t}+2C_2\\cos{2t}\\right)+0.1t-0.007\\\\[0.3cm]\nx'(0)=0=-0.14\\cdot C_1+2C_2-0.007\\to\\\\[0.3cm]\n2C_2=0.14\\cdot1.5+0.007=0.217\\to \\boxed{C_2=0.1085}"
Final result :
"\\boxed{x(t)=e^{-0.14t}\\left(-1.5\\cos(2t)+0.1085\\sin(2t)\\right)+0.05t^2-0.007t+2.42}"
ANSWER :
(a) model
"29.03\\cdot x''+8\\cdot x'+116.72\\cdot x=29.03\\cdot 9.81+6t^2\\\\[0.3cm]\nx(0)=l_0\\approx0.92\\,m\\\\[0.3cm]\nx'(0)=0"(b) solution
"x(t)=e^{-0.14t}\\left(-1.5\\cos(2t)+0.1085\\sin(2t)\\right)+0.05t^2-0.007t+2.42"
(c) graph
For small times "0\\le t\\le 10"
For large times "0\\le t\\le 50"
Comments
Leave a comment